Literature as Struggle: Variations on “The Death of the Author” - Todd, Elisabeth (Romance eReview, 2017)
Despite the title of Roland Barthes’ essay “The Death of the Author,” its treatment of literature is not entirely mortal: the author figure may be toppled, but from the rubble the reader is born. Still, the title references only a singular death, the “Death” of the author as a modern figure; in other words, any struggle between author and reader is neatly concluded. I propose to use a reading of Paul de Man’s “Literary History and Literary Modernity” not only to gain a better understanding of what is meant by the word ‘modern’, but to challenge – through a close reading of “The Death of the Author” as well – the singularity of the author’s death. De Man’s presentation of modernity and literature relies on the idea of a temporal paradox that is the source of an unresolved struggle; Barthes, on the other hand, seems to eschew the problem of temporality in the modern author’s mortality. Yet, in light of the presence of a second figure, the reader born upon the author’s death, it will be shown that there is an eternal struggle inherent in the foundation of “The Death of the Author.” And this struggle, after de Man, is a literary necessity. Literature exists in the promise of this combat, which, contrary to the title of Barthes’ essay, will not necessarily result in the author’s clean death. For literature as a struggle and as a gamble is just that: uncertain, risky, and yet something worthwhile.